Sudafricani, coloured, griqua: i cerchi concentrici di David’s Story (Altre Modernità, 2019)
Invaded, displaced, and dispossessed, the aboriginal Khoisan populations of South Africa were enslaved and pushed to the margins of society well before the arrival of European settlers in the seventeenth century; actually, the Bantu groups which had invaded southern Africa in the previous centuries had colonised various regions, due to their physical and military superiority. In contemporary South Africa, the condition of these people is still precarious, judging from the various forms of political protest reclaiming full citizenship for Khoisan communities. In some cases, however, the re-reading of History on the part of minority groups to obtain social and political recognition tends to reproduce, and therefore to confirm, the stereotypes and simplifications that contributed to their marginalisation in the first place. The case of the Khoikhoi populations in South Africa – classified as ‘coloured’, but still claiming specific ethnic identities of their own – is read here through the lens of literature, and specifically through the novel David’s Story by Zoë Wicomb – a South African writer who has always avoided the trap of simplism both as narrator and as social and literary critic.
Keywords: South Africa; Wicomb; narrative; History; Khoisan